EFFECT OF FUNGAL AND BACTERIAL BIOAGENTS AGAINST ALTERNARIA ALTERNATA (FR.) KEISSLER IN VITRO CONDITION - B. RAJPUT , K. U. SOLANKY, V. P. PRAJAPATI, D. M. PAWAR ,S. R. SURADKAR, (The Bioscan, 2013)
Investigation on leaf spot disease (Alternaria alternata (FR.) Keissler) of Brinjal (Solanum melongena L.) under south Gujarat condition was carried out to find out suitable management strategies. Due to hazardous effect of chemical fungicides, search for safer alternative to control the pathogen is better choice. This led to trials on the use of bioagents to control the pathogen. The eight known bioagents were evaluated by dual culture, pathogen at periphery and pathogen at the centre technique to monitor antagonistic effect. The results revealed that out of all the eight bioagents used, three bioagents viz., Trichoderma viride (IARI isolate) (74.77%, 69.04% and 79.45%), Trichoderma viride (Navsari isolate) (74.14%, 66.08%, and 76.99%) maximum growth inhibition in dual culture, pathogen at periphery and pathogen at the centre methods respectively), T. harzianum (Junagadh isolate) (71.25%, 59.96% and 74.78%) maximum growth inhibition in dual culture, pathogen at periphery and pathogen at the centre methods respectively, showed strong antagonistic effect to inhibit the mycelia growth of the pathogen significantly.